Pengembangan E-Modul PKN Materi Arti Gambar pada Lambang Negara Indonesia Kelas III Sekolah Dasar - Rusnaini, Rusnaini; Cahyono, Anang Hadi; Puniman, Achmad (Scholarly Journal of Elementary School, 2023)
This study aims to develop the PKN E-Module meaning the image on the Indonesian state symbol "Garuda Pancasila" as teaching material in the process of learning activities in schools and online learning. The research method used is Research and Development with the 4-D (Four-D) development model which is modified into three stages, namely the define stage, the design stage and the development stage. the stage of dissemination (disseminate) was not used due to limitations in the study. The developed PKN E-Module contains material on the meaning of the image on the Indonesian state symbol "Garuda Pancasila". The trial used in this study used a large-scale initial trial. The test subjects in this study were 19 grade III elementary school students. The results of this development research can be seen from the results of expert validation in the form of a Likert scale questionnaire and student responses using the Ghuttman scale questionnaire. The results of the material validation get a percentage of 93.18% in the proper category. The results of the design expert validation get a percentage of 97.5% in the feasible category. Student responses received positive responses in the initial large-scale trials which can be seen from the average results of 99% in the very good category. From these data, the PKN E-Module material for the meaning of images on the Indonesian state symbol for class III elementary schools is declared suitable for use as teaching material.